Rab1b Interacts with GBF1 and Modulates both ARF1 Dynamics and COPI Association - Monetta, Pablo Miguel (2007)
Assembly of the cytosolic coat protein I (COPI) complex at the ER-Golgi interface is directed by the ADP ribosylation factor1 (Arf1) and its guanine nucleotide exchange factor (GBF1). Rab1b GTPase modulates COPI recruitment, but the molecular mechanism underlying this action remains unclear. Our data reveal that in vivo expression of the GTP-restricted Rab1b mutant (Rab1Q67L) increased the association of GBF1 and COPI to peripheral structures localized at the ER exit sites (ERES) interface. Active Rab1b also stabilized Arf1 on Golgi membranes. Furthermore, we characterized GBF1 as a new Rab1b effector, and showed that its N-terminal domain was involved in this interaction. Rab1b small interfering RNA oligonucleotide assays suggested that Rab1b was required for GBF1 membrane association. To further understand how Rab1b functions in ER-to-Golgi transport, we analyzed GFP-Rab1b dynamics in HeLa cells. Time-lapse microscopy indicated that the majority of the Rab1b-labeled punctuated structures are relatively short-lived with limited-range movements. FRAP of Golgi GFP-Rab1bwt showed rapid recovery (t(1/2) 120 s) with minimal dependence on microtubules. Our data support a model where Rab1b-GTP induces GBF1 recruitment at the ERES interface and at the Golgi complex where it is required for COPII/COPI exchange or COPI vesicle formation, respectively.